U Shield 3 Axis CNC Router Training in Tegal City Metal Group to Improve Machinery Capability - Irfan Santoso; Galuh Renggani Wilis; Muhammad Agus Shidik (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: One of the main problems for small and medium industries (IKM) is limited capital. The average workforce is only junior high school graduates so that they lack competence and ability to improve product quality that can only compete at the local level.Contribution: The improvement of the small and medium industries (IKM) of Tegal City, especially those engaged in the metal sector, is the responsibility of the relevant agencies and universities.Method:  The formulation of the problem taken from this activity is how the training model for the operation of the U Shield 3 axis CNC Router machine is and how the enthusiasm of the participants for this service activity is. The method used is Soft Program and Hard Program.Results: The results of this training activity showed that participants understood the material presented, especially NC-based machines and its development. They also understood the role of the relevant agencies in the progress of the metal industry in Tegal City. In addition, the participants could practice the machine well, and the enthusiasm for this training was very good. It was proven by their desire so that activities like this could be carried out again, specifically discussing image design training. Conclusion: This activity can establish cooperation between universities, small and medium industries, and the Department of Industry and Trade of the City of Tegal